Propuesta de un sistema integrado de gestión para la empresa SGS ETSA fundamentado en los requisitos de la norma NTC-ISO 9001: 008 e ISO 27000 para el contrato No. 0010649 (2013)
The hydrocarbons sector in Colombia has stood out for promoting the economic growth of the country, generating the increase of resources that territorial entities receive for oil and gas production and foreign investment that has been increased by 89% compared to year 2010. Figures that are reflected in a source of income and permanent employment for large companies and multinationals. The SGS Group is the world's largest organization in the fields of Inspection, Verification and Testing. Founded in 1878, it has expanded all over the world, operating in more than 140 countries. The SGS Group is unique, not only because of its geographic coverage, but also because of the range of services it offers. In Colombia it has been operating since 1956 and since 1976, under the corporate name SGS Colombia S.A. and as a direct subsidiary of the Group, it opens offices in Bogotá and the main cities of the country. SGS Colombia S.A. is a global provider of technical verification, inspection, testing and appraisal compliance services, instilling confidence in customers. We ensure that the quality and development of your products or facilities comply with the applicable requirements, whether regulatory, voluntary or customer specifications. The goal is to help improve the integrity, quality and efficiency of equipment, ensure the safety and welfare conditions of workers and minimize the impact of industrial activities. These services are applied in engineering, construction projects, improvement in maintenance activities. Employees in the Industrial Services sector are the best qualified and recognized experts in the industry. We have decades of experience, our work is recognized by numerous accreditations by international organizations as well as standard specifications of our clients. Our experience can help you improve the conditions of your employees in safety and health, and in the impact of your activities. TECHNICAL STUDIES S.A. is an engineering company founded in 1964 with the purpose of providing engineering services to seek, define and implement comprehensive, innovative and economic solutions to the complex problems that development poses to the public and private sectors, inside and outside the country. Since its foundation, it has carried out works in the areas of Design, Intervention, Studies, and Consulting, Basic and Detail Engineering, Project Management and Construction, Industrial Appraisals and Inspection of Manufacturing and Assembly of Equipment throughout the Colombian territory, contributing to the development of the country. Several of his works have been executed in consortium with national firms or in consortium or with advice from foreign firms. A significant number of projects that have been worked on have been financed with loans from entities such as the Inter-American Development Bank (IDB), the International Bank for Reconstruction and Development (IBRD) and the United Nations Development Program (UNDP). SGS ETSA is currently developing several macro contracts with Ecopetrol S.A. that open the doors and position it as a leading company in the market. With the need for expansion and to provide a service that satisfies the expectations of its customers, SGS ETSA requires the implementation of an integrated management system that allows it to obtain optimum performance in its commercial activity, bringing with it economic benefits, the optimization of its resources through efficiency and effectiveness in the exercise of their work. With the expansion of the market it has become necessary to implement methodologies that allow organizations to be more competitive, not only nationally but internationally, being of vital importance the satisfaction of the client in all its aspects. With the implementation of quality systems based on ISO 9001 version 2001, companies take a step forward in the development of administrative systems based on Integral Management, which in the medium and long term results in their survival and growth. SGS ETSA aware of that need has been directed to the achievement of the quality of its products for this specific case it is decided to implement an integral system that adapts to the design for each hydrocarbon project; it is for this reason that it is decided to carry out the design of the integral management system ISO 9001 ISO 27000, taking as an example and field of investigation the Contract No. 0010649 whose object is "Civil, electrical and piping designs for the facilities of the campaign of drilling of the vice presidency of exploration and production validity 2013 ".